Analysis of a ground source heat pump system using an unsaturated 3-dimensional model. (5th February 2017) - Shang, Yan; Dong, Ming; Li, Sufen; Mu, Lin
Highlights: Unsaturated 3D model of GSHP system shows a better agreement with experimental data. The soil thermal effect radius increased about 27% considering infiltration. Soil temperature decreased as infiltration impact factors increasing in shallow soil. The evaporation effect on the soil temperature is obvious in the shallow depth. Abstract: This research presents an unsaturated three-dimensional model to study a ground source heat pump system based on moisture porous theory and soil moisture dynamics. The experiments are performed under the same condition as in the numerical methods. The soil temperature along 50 m deep of the U tube shows good agreement with the simulation results. The shallow soil temperature decreases by approximately 0.5–0.9 °C, during the heating period, when the infiltration and evaporation are considered by adding a source phase equation on the same operation time. The infiltration-influencing factors (e.g. soil moisture rate and soil saturated hydraulic conductivity) and the evaporation-influencing factors (e.g. soil saturated moisture content) are also calculated. The soil temperature decreases by approximately 5–8% as the influencing factors increase by 50–100%. Furthermore, the effect on the shallow soil is obvious, especially at a depth of 5 m and attenuates with the soil depth.